Construction of an integrated sexual function questionnaire for women with breast cancer - Cherng-Jye Jeng; Ming-Feng Hou; Hsing-Yuan Liu; Lih-Rong Wang; Jian-Jhou Chen (Elsevier, 2020)
Objective: With the increasing incidence of breast cancer in young women, its side effects have extended into the sexual lives of women. However, an appropriate tool to measure the sexual function is nonexistent. The aim of this study was to develop a suitable tool to measure sexual function in women with breast cancer. Materials and methods: After conducting literature reviews regarding the sexual function characteristics of women with breast cancer, this study designed a set of integrated sexual function questionnaires, which included pertinent information and three scales. The validity of the scales was examined under the guidance of three gender studies experts and two gynecologists who are also professors. Regarding the construct validity, researchers conducted exploratory factor analysis on the measurement results of 196 women with breast cancer. Results: The integrated sexual function questionnaires included the following three scales: "Breasts' Role Self-Checklist," "Scales for Breasts' Role in the Foreplay," and "Female Sexual Function Scale for BCSs." The questionnaire tool consisted of the longitudinal time change, patients' and their partners' situation, information related to the recovery process, participants' perspective toward objectification of women's breasts, the role of breasts in foreplay during sexual activities, sexual desire, sexual satisfaction, sexual obstacle, and other self-evaluations. We first derived one factor from six questions in "Breasts' Role Self-Checklist" and named it as "The Importance of Breasts for Women." The other two factors were obtained from eight questions in "Scales for Breasts' Role in the Foreplay" and named as "Sexual Attraction to Breasts" and "Function of Breasts in Foreplay." In addition, three factors were derived from 16 questions in "Female Sexual Function Scale for BCSs" and named as "Sexual Desire," "Sexual Satisfaction," and "Sexual Obstacle." Conclusion: This study determined that these integrated scales for breast cancer survivors are suitable due to their content validity, construct validity, and high internal consistency reliability, with a Cronbach's alpha of higher than 0.9 for all the three scales.